УТИЦАЈ ЗЕЛЕНЕ НАКНАДЕ, ЗЕЛЕНЕ ОЦЕНЕ И ЗЕЛЕНОГ ЗАДОВОЉСТВА НА ПЕРФОРМАНСЕ ЗАПОСЛЕНИХ У ГРАЂЕВИНСКИМ ПРЕДУЗЕЋИМА - SAPUTRI, Ira Septi Ayu; SAPUTRA, Asep Rokhyadi Permana; SUSANTO, Djaelani (Journal of process management and new technologies, 2024)
This inquire about points to analyze the impact of green compensation, green appraisal, and green satisfaction on employee performance in development companies in Indonesia. This research was conducted using a quantitative approach with a population of 8,769,798 employees working in Indonesian construction companies, then calculated using the Slovin formula to obtain a sample of 204 respondents. The sampling method in this research is non-probability using the Quota Sampling technique. The analysis technique uses a questionnaire in the form of a Google form which is distributed randomly to construction companies, and data testing uses an analysis tool in the form of PLS ​​SEM. The research results prove that (1) green compensation has no effect on employee performance in construction companies, (2) green compensation has a positive and significant effect on green satisfaction in construction companies, (3) green appraisal has a positive and significant effect on green satisfaction in construction companies, (4) green appraisal has a positive and significant effect on employee performance in construction companies, (5) green satisfaction has a positive and significant effect on employee performance in construction companies in Indonesia.